2009
DOI: 10.1534/genetics.109.107409
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular-Cytogenetic Method for Locating Genes to Pericentromeric Regions Facilitates a Genomewide Comparison of Synteny Between the Centromeric Regions of Wheat and Rice

Abstract: Centromeres, because of their repeat structure and lack of sequence conservation, are difficult to assemble and compare across organisms. It was recently discovered that rice centromeres often contain genes. This suggested a method for studying centromere homologies between wheat and rice chromosomes by mapping rice centromeric genes onto wheat aneuploid stocks. Three of the seven cDNA clones of centromeric genes from rice centromere 8 (Cen8), 6729.t09, 6729.t10, and 6730.t11 which lie in the Cen8 kinetochore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Although O. sativa and O. brachyantha separated each other for more than 15 million years and left <10% sequence conserved at the flanking regions of centromeres, our comparative analysis revealed that centromere synteny between these two Oryza genomes is still well maintained with the exception of a few subtle changes. This conservation can even extend to more distantly related grass species, such as B. distachyon, sorghum, maize, and wheat (Triticum aestivum; Qi et al, 2009Qi et al, , 2010Wang and Bennetzen, 2012). Therefore, from a genomic perspective, the location of the plant centromeres as observed here is unlikely to change substantially, supporting the view that chromosomal location may be an evolutionarily conserved primary determinant for functional centromere identity (Thakur and Sanyal, 2013).…”
Section: Conservation Of Centromere Locationsupporting
confidence: 70%
“…Although O. sativa and O. brachyantha separated each other for more than 15 million years and left <10% sequence conserved at the flanking regions of centromeres, our comparative analysis revealed that centromere synteny between these two Oryza genomes is still well maintained with the exception of a few subtle changes. This conservation can even extend to more distantly related grass species, such as B. distachyon, sorghum, maize, and wheat (Triticum aestivum; Qi et al, 2009Qi et al, , 2010Wang and Bennetzen, 2012). Therefore, from a genomic perspective, the location of the plant centromeres as observed here is unlikely to change substantially, supporting the view that chromosomal location may be an evolutionarily conserved primary determinant for functional centromere identity (Thakur and Sanyal, 2013).…”
Section: Conservation Of Centromere Locationsupporting
confidence: 70%
“…Another chromosome-specific marker, OSJNBa0088I16, was located near the end of the short arm of chromosome 11. It was proved that a distinct homology of segments located at the end of the short arms of chromosomes 11 and 12 by sequence analysis (Qi et al 2009). We found OSJNBa0088I16 hybridization signals were constantly detected on the short arm of chromosome 12.…”
Section: Identification Of Each Chromosome In Haploid Ricementioning
confidence: 66%
“…In addition, it was found that non-homologous chromosomes containing homologous fragments more easily paired in haploid rice cells during meiosis. Sequence data from the rice genome indicate a distinct homology of segments located at the end of the short arms of chromosomes 11 and 12 (Qi et al 2009), making these chromosomes, along with 11 and 12, more amenable to pairing. Besides, the normal function of meiosis-related proteins, REC8, PAIR2, and ZEP1, may promote the pairing of non-homologous chromosomes in haploid rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, for the known Gc factors, we have repeated backcrossing for several decades, but we could not separate 'breaking' and 'protecting' factors by recombination. Synteny of orthologous genes between wheat and rice revealed high conservation and a one-to-one correspondence of centromeric regions between chromosome 3B of wheat and chromosome 1 of rice (Qi et al, 2009). For the centromeric region of chromosome 1 in rice, distortion of marker segregation has been found in the F 2 population of indica-japonica hybrids (Harushima et al, 2001).…”
Section: Discussionmentioning
confidence: 99%